MENINGKATKAN PRESTASI BELAJAR MATEMATIKA DENGAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING - Mustasyfiyah, Mustasyfiyah (Universitas Negeri Surabaya, 2019)
This research to describe the student learning achievement with the Problem Based Learning Model in class XI MM 2 consists of 12 female students and 17 male students. This research uses the Classroom Action Research (CAR) method with 4 stages, namely: Planning, Acting, Observing, and Reflecting. Data sources in this research are students and teachers. The type of data collected includes student achievement data. The data was obtained by a test method and a documentation method. Data analysis technique is student achievement. All data are analyzed and it can be concluded that the Problem Based Learning model can improve mathematics learning achievement. In cycle I, mastery learning by 64% increased to 76.2% in cycle II. The increase in the average value of the class in cycle I of 59.8 increased to 78.33 in cycle II. The activeness of students during the learning process using the PBL learning model also increased. The biggest increase occurred in doing LKS. Students are more active in discussions and present problems that have been resolved.